1997
DOI: 10.1086/513799
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Anti‐GM1and Anti‐GQ1bGanglioside Antibodies in Guillain‐Barré Syndrome

Abstract: Anti-GM1 and anti-GQ1b ganglioside antibodies are found in association with acute and chronic peripheral neuropathies, including Guillain-Barré syndrome. They are believed to arise as a result of molecular mimicry with immunogenic microbial polysaccharides. Although anti-ganglioside antibodies are suspected to play a causal role in neuropathy pathogenesis, the details of this have yet to be proven. The approach in this laboratory to solving this issue has been to generate anti-GM1 and anti-GQ1b monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 3 publications
1
24
0
1
Order By: Relevance
“…Numerous investigators over several decades and several continents have attempted to determine whether these antibodies are pathogenetic and how they mediate damage. In summary, many collaborative efforts have demonstrated that anti-GM1 and anti-GQ1b antibodies bind to peripheral nerve and neuromuscular junctions 64,65 , and anti-GD1a antibodies bind to the nodes of Ranvier, paranodal myelin and neuromuscular junction 66,67,68 . Upon binding, the antibodies activate the complement cascade, resulting in formation of the membrane attack complex, disruption of sodium channel clusters at the node of Ranvier with disruption of nodal architecture 69 , and calcium influx and calpain-dependent neuronal and glial injury at the neuromuscular junction 70,71 .This injury can be ameliorated with complement inhibitors 72,73 .…”
mentioning
confidence: 99%
“…Numerous investigators over several decades and several continents have attempted to determine whether these antibodies are pathogenetic and how they mediate damage. In summary, many collaborative efforts have demonstrated that anti-GM1 and anti-GQ1b antibodies bind to peripheral nerve and neuromuscular junctions 64,65 , and anti-GD1a antibodies bind to the nodes of Ranvier, paranodal myelin and neuromuscular junction 66,67,68 . Upon binding, the antibodies activate the complement cascade, resulting in formation of the membrane attack complex, disruption of sodium channel clusters at the node of Ranvier with disruption of nodal architecture 69 , and calcium influx and calpain-dependent neuronal and glial injury at the neuromuscular junction 70,71 .This injury can be ameliorated with complement inhibitors 72,73 .…”
mentioning
confidence: 99%
“…Earlier studies demonstrated the lack of binding of monoclonal anti-GM2 antibodies with O:23 LPS in Western blot or TLC, indicating the absence of a GM2-mimic (28,39). Another explanation may be that differences in the density of GM2-mimics and the adjuvant properties of the lipid A portion and/or O-chain influence the induction of antiglycolipid antibodies and the presentation of the GM2-mimics in the Western blot between the O:1, O:23, and O:36 serostrains (28,33).…”
Section: Discussionmentioning
confidence: 99%
“…The Guillain-Barré syndrome (GBS) and Miller Fisher syndrome (MFS) are frequently preceded by an infection with C. jejuni, and GBS and MFS patients have crossreactive antibodies against LPS and gangliosides (16,36). These antibodies have been implicated to play a role in the pathogenesis of both neurological diseases (30,33). In contrast to patients with GBS and MFS, patients with an uncomplicated C. jejuni enteritis do have a low-titer antibody response against LPS, but they do not have a cross-reactive antiglycolipid response (10,15).…”
mentioning
confidence: 99%
“…Mimicry between cardiac myosins, other a helical proteins such as laminin and tubulin, the streptococcal carbohydrate and M protein is the most likely aetiology of the disease (Cunningham, 2000;Galvin et al, 2000;Kirvan et al, 2003Kirvan et al, , 2007. Other autoimmune diseases associated with a potential infectious aetiologies include insulin-dependent diabetes mellitus (Tian et al, 1994;von Herrath et al, 2003), ankylosing spondylitis (Fielder et al, 1995), Guillain-Barre syndrome (Oomes et al, 1995;Willison et al, 1997Willison et al, , 2008Goodyear et al, 1999;Hartung et al, 2002;Jacobs et al, 2002Jacobs et al, , 2008, primary biliary cirrhosis (Shimoda et al, 1995) and multiple sclerosis (Wucherpfennig and Strominger, 1995;von Herrath et al, 2003). The rheumatic autoimmune diseases include systemic lupus erythematosus (James et al, 1997;Arbuckle et al, 2003), rheumatoid arthritis (Holoshitz et al, 1986), Sjogren syndrome (Talal, 1990) and others are potentially due to an infectious aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…Specific monoclonal antibody molecules may recognize peptides and carbohydrates Shikhman and Cunningham, 1997), carbohydrates and deoxyribonucleic acid (DNA) (Kabat et al, 1986) or proteins and DNA (Cunningham and Swerlick, 1986;Gaynor et al, 1997;Putterman and Diamond, 1998). Gangliosides are also found to be important targets of antibodies against the group A streptococcal carbohydrate (Kirvan et al, 2003) or lipopolysaccharide components of Campylobacter jejuni in Guillain-Barre syndrome (Willison and Kennedy, 1993;Willison et al, 1997Willison et al, , 2008Goodyear et al, 1999). The basis of these diverse crossreactions may be due in part to structural characteristics of the antigenic epitope as well as germline configurations of the antibody molecule.…”
Section: Introductionmentioning
confidence: 99%